High-frequency irreversible electroporation improves survival and immune cell infiltration in rodents with malignant gliomas - Campelo, Sabrina N.; Lorenzo, Melvin F.; Partridge, Brittanie; Alinezhadbalalami, Nastaran; Kani, Yukitaka; Garcia, Josefa; Saunier, Sofie; Thomas, Sean C.; Hinckley, Jonathan; Verbridge, Scott S.; Davalos, Rafael V.; Rossmeisl, John H. (Frontiers in Oncology, 2023)
Background: Irreversible electroporation (IRE) has been previously investigated in preclinical trials as a treatment for intracranial malignancies. Here, we investigate next generation high-frequency irreversible electroporation (H-FIRE), as both a monotherapy and a combinatorial therapy, for the treatment of malignant gliomas. Methods: Hydrogel tissue scaffolds and numerical modeling were used to inform in-vivo H-FIRE pulsing parameters for our orthotopic tumor-bearing glioma model. Fischer rats were separated into five treatment cohorts including high-dose H-FIRE (1750V/cm), low-dose H-FIRE (600V/cm), combinatorial high-dose H-FIRE + liposomal doxorubicin, low-dose H-FIRE + liposomal doxorubicin, and standalone liposomal doxorubicin groups. Cohorts were compared against a standalone tumor-bearing sham group which received no therapeutic intervention. To further enhance the translational value of our work, we characterize the local and systemic immune responses to intracranial H-FIRE at the study timepoint. Results: The median survival for each cohort are as follows: 31 days (high-dose H-FIRE), 38 days (low-dose H-FIRE), 37.5 days (high-dose H-FIRE + liposomal doxorubicin), 27 days (low-dose H-FIRE + liposomal doxorubicin), 20 days (liposomal doxorubicin), and 26 days (sham). A statistically greater overall survival fraction was noted in the high-dose H-FIRE + liposomal doxorubicin (50%, p = 0.044), high-dose H-FIRE (28.6%, p = 0.034), and the low-dose H-FIRE (20%, p = 0.0214) compared to the sham control (0%). Compared to sham controls, brain sections of rats treated with H-FIRE demonstrated significant increases in IHC scores for CD3+ T-cells (p = 0.0014), CD79a+ B-cells (p = 0.01), IBA-1+ dendritic cells/microglia (p = 0.04), CD8+ cytotoxic T-cells (p = 0.0004), and CD86+ M1 macrophages (p = 0.01). Conclusions: H-FIRE may be used as both a monotherapy and a combinatorial therapy to improve survival in the treatment of malignant gliomas while also promoting the presence of infiltrative immune cells.